Synthesis and Anti-proliferative Activity of Substituted-Anilinoquinazolines and Its Relation to EGFR Inhibition - Ella, D. A. A El; Saleh, K. A.; Hassan, M.; Hamdy, N.; El-Araby, M. E.; Abouzid, K.A. M. (Arzneimittelforschung, 2012)
4-Anilinoquinazoline is a privileged scaffold in developing small molecule inhibitors of tyrosine kinases (TK) especially epidermal growth factor receptor (EGFR). 2 series belonging to 3'-substituted-4-anilinoquinazoline scaffold were synthesized and screened in vitro on isolated and a breast cancer cell line. The research aims at exploring the activity of compounds having diverse substituents at 3' position of the aniline moiety. Generally, the meta-substituted-anilinoquinazolines exhibited significant inhibitory activity against isolated enzyme as well as MCF-7 cancer cell line. For instance, compound 10b inhibited >99% of EGFR activities at 10 µM concentration. 6 of the tested compounds exhibited range of anti-proliferative activity below 10 µM potency. In particular, compounds 6e and 10b displayed the highest activity among the tested compounds with IC50 values equal to 8.6 and 4.84 µM, respectively. Structure-based tools were utilized to rationalize EGFR-TK binding of compound 10b since it is the most active compound in the enzyme inhibition test.
Keywords: quinazoline; anilinoquinazoline; EGFR inhibitors; tyrosine kinase inhibitors; anti-cancer; structure-based design